1988
DOI: 10.1021/bi00410a048
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of tRNAs and of phosphorothioate-substituted nucleic acids with an organomercurial. Probing the chemical environment of thiolated residues by affinity electrophoresis

Abstract: The interactions of 4-thiouridine and 5-[(methylamino)methyl]-2-thiouridine in tRNA and of phosphorothioate esters in nucleic acids with an organomercurial have been investigated. For this purpose, an affinity electrophoretic system has been developed in which the mercury derivative has been covalently immobilized in a standard polyacrylamide gel. The retardation of thiolated macromolecules was found to be sensitive to the chemical environment of the sulfur atom, giving characteristic interaction constants dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 40 publications
1
147
0
2
Order By: Relevance
“…To see whether the 2-thiolation occurred specifically on tRNA LYS , we used the APM/PAGE band shift method, which relies on the strong retardation of thiolated tRNA in electrophoresis because of the affinity of the thio group with the mercuric compound (APM) in the gel (22). These experiments showed that the tRNA LYS , but not the tRNA MET , which has a C at position 34, was thiolated in vivo in S. pombe and C. elegans and that the thiolation was absent in a ctu1 mutant from either species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To see whether the 2-thiolation occurred specifically on tRNA LYS , we used the APM/PAGE band shift method, which relies on the strong retardation of thiolated tRNA in electrophoresis because of the affinity of the thio group with the mercuric compound (APM) in the gel (22). These experiments showed that the tRNA LYS , but not the tRNA MET , which has a C at position 34, was thiolated in vivo in S. pombe and C. elegans and that the thiolation was absent in a ctu1 mutant from either species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…T7 RNA polymerase was purified from strain BL21(pAR219), which was a generous gift of F. Studier. Acryloyl aminophenylmercury(II) chloride (APM) for affinity electrophoresis was prepared as described previously (31) and used as a stock solution of 1 mg/ml in formamide. L-[ 35 S]Cysteine was obtained from PerkinElmer Life Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…APM Affinity Gel Assays with Sulfide as Substrate-For reactions with sulfide as sulfur source, a gel shift assay using APM polyacrylamide gels was used based on the work of Igloi (31). This technique incorporates APM into the polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). [9][10][11] The mobility of RNA that carry thiophosphate monoester is diminished, compared with non-thiophosphated one. This is the evidence of the strong interaction between mercury and sulfur.…”
Section: Journal Of the Korean Chemical Societymentioning
confidence: 99%